Comprehensive Assessment of Anti-Inflammatory, Antiproliferative and Neuroprotective Properties of Cauliflower after Dehydration by Different Drying Methods - Antonio Vega-Galvez; Alexis Pasten; Elsa Uribe; Nicol Mejias; Michael Araya; René L. Vidal; Gabriela Valenzuela-Barra; Carla Delporte (Foods)
Cauliflower (Brassica oleraceae L. var. Botrytis Linnaeus) has various health benefits due to its rich bioactive compound content. However, this fresh vegetable faces challenges related to its perishability and short shelf life. This study explores the effect of five drying methods, namely vacuum drying (VD), convective drying (CD), infrared drying (IRD), low-temperature vacuum drying (LTVD) and vacuum freeze-drying (VFD), on the bioactive compounds and health-promoting properties of cauliflower. Analyses of amino acids, hydroxycinnamic acid and its derivatives, glucosinolates, and isothiocyanates, as well as evaluations of their anti-inflammatory, antiproliferative, and neuroprotective properties, were conducted based on these five drying methods. The results revealed that samples treated with VFD and IRD had a higher content of amino acids involved in GSL anabolism. Moreover, VFD samples retained hydroxycinnamic acid derivatives and glucosinolates to a greater extent than other methods. Nonetheless, the CD and VD samples exhibited higher antiproliferative and neuroprotective effects, which were correlated with their high sulforaphane content. Overall, considering the retention of most bioactive compounds from cauliflower and the topical inflammation amelioration induced in mice, VFD emerges as a more satisfactory option.